QUALITY OF LIFE OF TYPICALLY DEVELOPING SIBLINGS OF PEOPLE WITH PROFOUND INTELLECTUAL AND MULTIPLE DISABILITIES IN POLAND - Niedbalski, Jakub (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
Family quality of life (FQOL) is a concept that is gaining increasing importance in family support programmes. However, for some countries, this concept has been insufficiently explored in relation to families with children with intellectual and developmental disabilities. The aim of this study was to ascertain the perceived QOL of siblings of children with profound intellectual and multiple disabilities (PIMD) living in Poland. The study relies on a qualitative research approach. Semi-structured interviews were conducted with 18 siblings aged 6 to 15, followed by thematic analysis. The siblings identified the following nine domains as dimensions that impacted their QOL: joint activities, mutual understanding, private time, acceptance, forbearance, effect on well-being, exchanging experiences, social support, and dealing with the outside world. The children described both positive and negative experiences, indicating that having a sibling with intellectual and developmental disabilities affected their QOL in diverse ways.